A sense of belonging in Australian higher education : the significance of self-efficacy and the student-educator relationship. - Larsen, Ana; James, Trixie (Journal of University Teaching & Learning Practice v.19 n.4 https://doi.org/10.53761/1.19.4.5, 2022)
With recent massification policies and reforms, Australia's widening participation agenda has been instrumental in increasing participation of marginalised students in higher education. This paper considers how a sense of belonging can be instilled in marginalised students, improving retention and success and ultimately widening participation in higher education. It is recognised that one of the most important contributors to student engagement is the educator. Unfortunately, in academia today, educators are increasingly time-poor for several reasons including the neo-liberal nature of higher education, the COVID-19 pandemic and an emergency move to remote teaching. This article applies Bandura's concept of self-efficacy to highlight how, when nurtured effectively, the student-educator relationship can contribute to improving students' self-efficacy and their sense of belonging. Self-efficacy has been shown to affect aspirations, behavioural choices, maintenance of effort and affective reactions (Bandura, 1997), all of which can contribute to, or inhibit, students' academic success. Self-efficacy can be increased via four sources: mastery experiences, verbal persuasion, vicarious experiences, and emotional and physiological states (Bandura, 1997). Central to this discussion is the value of vicarious experiences as a conduit between the educator and student in developing a student's self-efficacy. This article provides practical advice for educators so they may focus their efforts and build strong student relationships in the most effective manner. [Author abstract]